2017
DOI: 10.2174/1874401x01710010023
|View full text |Cite
|
Sign up to set email alerts
|

Landlocked Fall Chinook Salmon Maternal Liver and Egg Thiamine Levels in Relation to Reproductive Characteristics

Abstract: Object:Landlocked fall Chinook Salmon Oncorhynchus tshawytscha in Lake Oahe, South Dakota, typically experience poor reproductive success. Introduction:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The significant difference in a* values between those spawns which experienced total mortality versus those where at least some of the eggs survived is of particularly interest. Doyle et al (2017) reported lower egg thiamine levels in landlocked fall Chinook salmon spawns which did not survive. Huysman et al (2018) observed that female salmon producing completely non-viable spawns may have been held for a slightly longer period of time prior to spawning, and that their spawns had relatively fewer eggs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The significant difference in a* values between those spawns which experienced total mortality versus those where at least some of the eggs survived is of particularly interest. Doyle et al (2017) reported lower egg thiamine levels in landlocked fall Chinook salmon spawns which did not survive. Huysman et al (2018) observed that female salmon producing completely non-viable spawns may have been held for a slightly longer period of time prior to spawning, and that their spawns had relatively fewer eggs.…”
Section: Discussionmentioning
confidence: 96%
“…The positive correlation between egg coloration values and survival, as well as the significantly greater a* (red) values in spawns which experienced at least some egg survival, may be temperature related. Chinook salmon in Lake Oahe experience elevated temperatures during egg development and maturation (Young et al, 2016;Doyle et al, 2017). In addition, spawning water temperatures are frequently above 15°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation